Developing digital scholarship: emerging practices in academic libraries - Mackenzie, Alison; Martin, Linsdsey (Facet Publishing, 2017)
This book provides strategic insights drawn from librarians who are meeting the challenge of digital scholarship, utilizing the latest technologies and creating new knowledge in partnership with researchers, scholars, colleagues and students.